2007
DOI: 10.1111/j.1365-2672.2006.03097.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Pediococcus spp. to antimicrobial agents

Abstract: Aim:  To investigate the susceptibility of Pediococcus species to antimicrobial agents. Methods and Results:  The susceptibility to 14 antimicrobial agents of 31 genotypically distinct strains of six Pediococcus species was assessed by using Etests on ISO‐sensitest agar supplemented with horse blood. The species included were Pediococcus acidilactici, Pediococcus damnosus, Pediococcus dextrinicus, Pediococcus inopinatus, Pediococcus parvulus and Pediococcus pentosaceus. For several antimicrobial agents, some s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
28
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 23 publications
10
28
2
Order By: Relevance
“…In this respect, Ammor et al [41] reported that pediococci are intrinsically resistant to the latter two antibiotics, as well as to glycopeptides (vancomycin and teicoplanin), streptomycin, ciprofloxacin and trimethoprim-sulphamethoxazole. Other authors proposed a MIC for tetracycline in pediococci ranging between 8 and 16 mg/L [42], or of 32 mg/L for oxytetracycline in P. pentosaceus [17]. The tetracycline breakpoints suggested for pediococci by EFSA are lower than the MICs observed in our work and others [17,42].…”
Section: Discussioncontrasting
confidence: 69%
“…In this respect, Ammor et al [41] reported that pediococci are intrinsically resistant to the latter two antibiotics, as well as to glycopeptides (vancomycin and teicoplanin), streptomycin, ciprofloxacin and trimethoprim-sulphamethoxazole. Other authors proposed a MIC for tetracycline in pediococci ranging between 8 and 16 mg/L [42], or of 32 mg/L for oxytetracycline in P. pentosaceus [17]. The tetracycline breakpoints suggested for pediococci by EFSA are lower than the MICs observed in our work and others [17,42].…”
Section: Discussioncontrasting
confidence: 69%
“…isolated from food are limited. Penicillin G, imipenem, gentamicin, netilmicin, erythromycin, clindamycin, rifampin, chloramphenicol, daptomycin, and ramoplanin are generally active against Pediococcus species [24-27]. However, susceptibility is thought to be species-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Rif r marking to recover introduced Lactobacillus strains from the indigenous GIT microbiota has been successfully used in chickens (23,43), ducks (16), pigs (22,39), mice (19,41), and humans (20,45), so a Rif r background was unexpected in this study. Rif MIC levels within several Lactobacillus and Pediococcus species have been reported to range between Յ0.016 and 4 g ml Ϫ1 (12,13). da Costa et al (10) investigated the level of antimicrobial resistance in enterococci in broiler feed and broiler feed ingredients and found 58 and 60%, respectively, of enterococcal isolates were resistant to 5-g Rif discs.…”
Section: Discussionmentioning
confidence: 99%